Elaboration of tables for concrete dosage based on the aggregates used in Northeast Mineiro (Research, Society and Development, 2018)
Given the gradual increase in the technological level of the production of inputs, machines and other things directly and indirectly related to the Civil Construction Industry, it is still necessary to study the characteristics of the materials of each region of the country and its applications to the concrete traces traditionally used. Several studies have shown that variations in aggregates alter the final properties of ready-mixed concrete, which makes it impossible to use general tables, as is customary in construction. In this perspective, the concrete dosage was applied applying aggregates of the region of the Brazilian city of Teófilo Otoni, located in the northeast of Minas Gerais. In the use of regional aggregates, as well as in the application of binders currently used in Brazil and other aspects addressed in this work, it is evident the need for regionally applicable studies such as this one, which brought results, which triggered the preparation of which may represent an advance in concrete manufacturing technology in the region, which can be applied to the site, facilitating engineering projects and bringing greater security to users and executors of future developments.